2014
DOI: 10.1371/journal.pone.0081301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features Related to HIV Integrase Inhibition Obtained from Structure- and Ligand-Based Approaches

Abstract: Among several biological targets to treat AIDS, HIV integrase is a promising enzyme that can be employed to develop new anti-HIV agents. The aim of this work is to propose a mechanistic interpretation of HIV-1 integrase inhibition and to rationalize the molecular features related to the binding affinity of studied ligands. A set of 79 HIV-1 integrase inhibitors and its relationship with biological activity are investigated employing 2D and 3D QSAR models, docking analysis and DFT studies. Analyses of docking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The 2D contribution maps identified a favored carbonyl-hydroxy-aromatic motif, and the 3D maps further suggested that bulky groups in the meta and para positions would increase its biological activity. Similar schemes can also be seen in the studies of Gupta et al [37] and de Carvalho et al [34]. For 3D-QSAR, the alignment of compound structures is an important step, although there is no golden rule.…”
Section: Function Of Inmentioning
confidence: 53%
See 3 more Smart Citations
“…The 2D contribution maps identified a favored carbonyl-hydroxy-aromatic motif, and the 3D maps further suggested that bulky groups in the meta and para positions would increase its biological activity. Similar schemes can also be seen in the studies of Gupta et al [37] and de Carvalho et al [34]. For 3D-QSAR, the alignment of compound structures is an important step, although there is no golden rule.…”
Section: Function Of Inmentioning
confidence: 53%
“…The data set was divided into two classes, either 'active' (pIC 50 > 4) or 'inactive' (pIC 50 < 4), and then partitioned into training and test sets. To take both structural diversity and pIC 50 distribution into consideration, Magalhas Ude et al [33] and de Carvalho et al [34] made a manual selection to ensure that both factors were well represented in both training and test sets.…”
Section: Function Of Inmentioning
confidence: 99%
See 2 more Smart Citations
“…All validation coefficients were evaluated according to acceptable reference values 9,11,32 . Our strategy was based on many works which combine different QSAR methods in the drug design [33][34][35][36][37][38] .…”
Section: Qsar Modelsmentioning
confidence: 99%